Hydrothermal synthesis of monoclinic WO3 nanoplates and nanorods used as an electrocatalyst for hydrogen evolution reactions from water - Ham D.J. (2014)
Monoclinic WO3 (m-WO3) nanoplates and nanorods were successfully synthesized by a simple hydrothermal process using sodium tungstate dihydrate (Na2WO4·2H2O), ammonium nitrate (NH4NO3) and polyethylene glycol (PEG) as initial precursors. Phase, morphologies and electrochemical properties of the products were characterized by X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM, TEM), high-resolution transmission electron microscopy (HRTEM), cyclic voltammetry (CV) and linear sweep voltammetry (LSV). The effect of NH4NO3 concentration on the formation of the pure phase of m-WO3 nanomaterial was studied. The product synthesized under NH4NO3-free condition was pure orthorhombic WO3·0.33H2O (o-WO3·0.33H2O) phase. By adding and increasing the amount of NH4NO3 to the solution, m-WO3 phase started to form and became pure m-WO3 phase when 1.50g NH4NO3 was used. The morphology of m-WO3 was nanoplates, and became nanorods by PEG adding. The nanostructured m-WO3 showed much higher electrocatalytic activity for hydrogen evolution from water than that of the commercial bulk m-WO3, including the m-WO3 nanorods with slightly better than the m-WO3 nanoplates. © 2010 Elsevier B.V.